Measuring aggregate morphologies based on three‐dimensional curvature analysis. (12th November 2021) - Wang, Feng; Xiao, Yue; Cui, Peide; Mo, Liantong
Abstract: Digital image processing has become the mainstream method for measuring aggregate morphologies. However, the results of the image method are seriously affected by the laying style of aggregates. This study proposes a morphological analysis method based on three‐dimensional curvature analysis. The results show that the values of maximum curvature and standard deviation of Gaussian curvature on the aggregate surface can be used to represent the angularity and texture, respectively. The relative ranking of methods according to the accuracy places the curvature method as the largest and the image method as the least, with the profile method falling in between. The proposed method could provide a new possibility to accurately quantify the aggregate morphologies and contribute to the design of the mixture. Better quality of asphalt pavement could be obtained by taking into account the comprehensive morphologies reported in this study.